Providing Data-Driven Equitable Palliative and End-of-Life Care for Structurally Vulnerable Populations: A Pilot Survey of Information Management Strategies. (April 2020) - Rajaram, Akshay; Morey, Trevor; Shah, Sonam; Dosani, Naheed; Mamdani, Muhammad
Background: Considerable gains are being made in data-driven efforts to advance quality improvement in health care. However, organizations providing hospice-oriented palliative care for structurally vulnerable persons with terminal illnesses may not have the enabling data infrastructure or framework to derive such benefits. Methods: We conducted a pilot cross-sectional qualitative study involving a convenience sample of hospice organizations across North America providing palliative care services for structurally vulnerable patients. Through semistructured interviews, we surveyed organizations on the types of data collected, the information systems used, and the challenges they faced. Results: We contacted 13 organizations across North America and interviewed 9. All organizations served structurally vulnerable populations, including the homeless and vulnerably housed, socially isolated, and HIV-positive patients. Common examples of collected data included the number of referrals, the number of admissions, length of stay, and diagnosis. More than half of the organizations (n = 5) used an electronic medical record, although none of the record systems were specifically designed for palliative care. All (n = 9) the organizations used the built-in reporting capacity of their information management systems and more than half (n = 6) augmented this capacity with chart reviews. Discussion: A number of themes emerged from our discussions. Present data collection is heterogeneous, and storage of these data is highly fragmented within and across organizations. Funding appeared to be a key enabler of more robust data collection and use. Future work should address these gaps and examine opportunities for innovative ways of analysis and reporting to improve care for structurally vulnerable populations.